Do women with benign versus malignant ovarian masses demonstrate variable clinical presentation? - Bagde, Nilajkumar D.; Bagde, Madhuri; Agrawal, Sarita; Lone, Zamir A.; Hussain, Nighat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Early diagnosis of ovarian tumors is a challenge due to variable presentation. Early diagnosis of ovarian cancers aids in timely management and better clinical outcomes. Aim of study was to determine the different clinical presentations of ovarian tumors and compare those in benign tumors versus malignancies. Methods: Clinical data of all women operated for ovarian masses was extracted from case files at a tertiary care centre and evaluated and clinical features compared in women with benign versus malignant tumors. Results: We found 50 cases of ovarian tumors with 26% malignancies. The mean age was 38.48+14.9 years. Malignancies were significantly common in menopausal than menstruating (χ2=13.57, p=0.001, fishers exact). Pain was the commonest symptom and combined lumbar and iliac pain was reported in 67% cases. The location of pain was not significantly different in women with malignancy compared to those with benign tumors (likelihood ratio χ2=7.93, p=0.24). The odds of reporting a mass in abdomen were significantly greater in women with cancers than benign tumors (OR= 4.9, 95%CI 1.07-24.06, p=0.01). More women with cancer had history of distension of abdomen compared to women with benign tumors (χ2=9.43, p=0.002). Conclusions: Lumbar pain is most frequent complaint in women with ovarian pathology. Symptoms of distension in abdomen or presence of lump in abdomen are a significant guide to alert the physician regarding possibility of malignancy must be evaluated without delay.